The Influence of Leadership Style, Organizational Culture, Work Discipline on Employee Performance in Government Offices - Maria Jashinta Elisabet Hamboer; Alamsyah Alamsyah; Iswahyu Pranawukir (Mediastima, 2023)
This study seeks to investigate the impact of leadership approach, corporate culture, and work ethics both individually and collectively on employee effectiveness. The data utilized in this study consist of primary and secondary data gathered from both fieldwork and library sources. The sample size for this study comprises 70 employees. This research is of a quantitative nature. The statistical analysis employed is multiple linear regression using SPSS 25. The findings of this study demonstrate that leadership approach, corporate culture, and work ethics have a significant effect on performance, both individually and collectively.